Introduction - Chung, Joseph (L'Actualité économique, 1975)
AbstractOne of the most significant post-war development in economics has been the contribution of econometrics to the refinement of techniques of analysis. Econometrics is now an integral part of economics teaching in most of the known universities throughout the world and large econometric models are being used for economic policies in industrialized countries. The CANDIDE model (Canadian Disaggregated Inter-Departmental Econometric Model) is a medium-term policy oriented model and an indication of some degree of maturity in the Art of model building in CANADA.The purpose of this special issue of L'Actualité Économique is to initiate undergraduate students in economics as well as the interested public to the model, to show how the model can be applied and finally to discuss some of its deficiencies. It is hoped that this special issue will be a useful tool for the teaching of econometrics in Canada. It has three parts. The first part comprising three papers, explains the nature and the characteristics of the model. The second part through five papers shows various applications of the model. Finally, in the third part, seven papers discuss some of the deficiencies of the major blocks of the model1.1 Only the first two parts are included in this issue. The third part will be published in the next issue.